Chacha stream cipher implementation for network security in wireless sensor network. (December 2019) - Muhammad, F; Ahendyarti, C; Masjudin,
Abstract: In the 4.0 industrial revolution, technologies are designed to be able to connect to the internet. These technologies should be able to exchange data between them using sensors and others. One of the ways to send it is by the wireless sensor network. However, involving the internet in exchanging data needs security guarantees. Three things must meet in network security, that is confidentiality, integrity, and availability. Cryptography use for the confidentiality of the information that will be sent by the user. In this research will be using the symmetric cryptography for network security on wireless sensor networks. In addition to network security, symmetric cryptography method will be used also consider energy efficiency on a wireless sensor network. Chacha stream cipher as symmetric cryptography will be used as a method of messages encryption. Experiments in this research used NS-3 as a network simulator. Results of the tests show that the purpose method has a computation time of 0.2385 ms and the second-fastest after the rabbit cryptographic process. Chacha LR WPAN simulation process has a computation time of 17.6199 ms.